Pengaruh Pemberian Maggot Terhadap Kandungan Hemoglobin Dan Kolesterol Ikan Nila (Oreochromis niloticus) - Reni Rakhmawati; Mei Sulistyoningsih; Ayatun Nisak (JURNAL ILMIAH AGRINECA, 2023)
Feed greatly affects the growth and survival of tilapia. Intensive fish farming requires commercial feed of the right quality, on time, and in the right amount. With increasing production costs, it is necessary to look for alternative protein sources that are cheaper and easier to obtain by using insects. This study aims to determine the effect of giving maggot on tilapia hemoglobin and cholesterol and its implementation in education. This study used a research design using a completely randomized design (CRD). Experiments in this study were carried out using 4 different treatments and 4 repetitions. The data analysis technique used is factorial anova using the SPSS application. The results showed that there was no significant effect of adding maggot feed to hemoglobin while there was a significant effect on cholesterol. evidenced by the SPSS factorial anova test results for hemoglobin of sig. 0.447 and for cholesterol sig. 0.00.